A Group-Based Program of Emotional Recovery for Younger Women Following Myocardial Infarction - Bowers, Michele J.; Buchanan, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2008)
Heart disease is the leading cause of illness, disability, and death among women in Canada. Myocardial infarction (MI) accounts for almost half of these deaths yearly. The purpose of this study was to understand younger women’s experience of recovery from MI. Apurposive sample consisting of six younger women diagnosed with MI participated in an eight-week guided autobiographical (GA) group intervention where they engaged in weekly reflection, writing, and group dialogue. The experience of loss, uncertainty, changesin self-perception, self-care, health care and support from others, and caring for others emerged from the data analysis. GA was shown to be an effective psychosocial intervention to facilitate emotional recovery following a significant cardiac event as all participants described the GA group as a therapeutic component of their recovery process.